Adoção do e-business entendida como inovação e seus impactos na logística: estudo de caso de uma multinacional brasileira versus multinacional de capital estrangeiro - Rosa, Marcelo Scorsato da (2012)
In this study, our objective was to verify the changes that occurred in logistics in the big companies with the adoption of the e-business, considered an innovation, comparing a multinational company of national capital and a company of foreign capital acting in Brazil. The comparison between domestic firms and subsidiaries are used to identify if subsidiaries bring knowledge on the use of the internet of their head offices and if that carts some difference in the logistics to serve to the e-business. So, it was identified: the needs that led companies to adopt the e-business, the main changes from the logistics of deploing this tool and finally, the difficulties of firms in adapting their logistics to this new use. The research approach is exploratory, qualitative in nature, using the method of case study. The technique for data collection used semi-structured interviews starting from a questionnaire based on the theoretical background as well as analysis of documents and secondary data, such as company websites, reports, among others. The result shows that the transfer of knowledge of the head office to the subsidiary and the organizational structure aligned to a global strategy of the foreign multinational gone back to the innovation collaborated for the success in the adoption of the e-business, what was not identified in the Brazilian multinational. The foreign multinational developed and adopted the e-business with own resources and training, and transformed the logistics to serve to the e-business, as a consequence of the operational and structural demands necessary to the new channel, while the Brazilian multinational looked for technical training in other places to adopt the innovation and, later, hired an logistics operator to execute the operations coming from the e-business. The difficulties to the adaptation of the logistics were identified in the two companies, above all in the distribution; the foreign multinational overcame with own knowledge and the Brazilian multinational needed the interaction with other companies.